Bismarck in the bedroom? Pension reform and fertility: Evidence 1870-2010 - Philipp Jäger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Rising public pension generosity has frequently been cited as one reason for the (persistently) declining fertility rates in many advanced economies. Despite the theoretical appeal, empirical evidence on the pension-fertility nexus is limited. To fill this gap, I study country-level fertility trends before and after 23 pension reforms using a long-run panel dataset starting in 1870. I find no evidence that pension reforms, on average, affect fertility in the way most theoretical models predict.
Keywords: H55; J13; 330